2001
DOI: 10.1093/humupd/7.5.473
|View full text |Cite
|
Sign up to set email alerts
|

Varicocele and male infertility: Part II: Pathophysiology of varicoceles in male infertility

Abstract: Varicoceles are found in 19 to 41% of infertile men, and is one treatable form of male infertility. The mechanism by which varicoceles cause the variable effect on male infertility and spermatogenesis is still unknown. Experimental animal models play a useful (but limited) role due to the sudden and variable iatrogenic nature of the varicoceles and the duration of the studies. Much of the human data are derived by the characterization of associated differences in measurable parameters between men with and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
264
2
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(278 citation statements)
references
References 112 publications
4
264
2
8
Order By: Relevance
“…The exact mechanism by which an incidental varicocele becomes pathological remains unclear (29). Recently, studies have demonstrated the role of oxidative stress in men with varicocele and infertility (30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact mechanism by which an incidental varicocele becomes pathological remains unclear (29). Recently, studies have demonstrated the role of oxidative stress in men with varicocele and infertility (30).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have looked for specific markers of testicular injury in infertile men with clinical varicoceles (29). Even though Dubin and Hotchkiss have described specific findings of germinal cell hypoplasia and premature sloughing of immature forms within the lumena of the seminiferous tubules in their study of 88 subfertile men with varicoceles, most of the reported changes in testicular histology and semen quality seen in these men are largely nonspecific (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to thermoregulatory failure, hypoxia due to venous stasis, high levels of oxidants, anti-sperm antibodies, reflux of renal and adrenal metabolites down the spermatic vein, and dilution of intra-testicular substrates, such as testosterone, were proposed to explain impairments in testicular function resulting from varicocele [27,28]. However, to gain more insight into molecular pathology of varicocele, evaluation of various metabolites, transcripts, and proteins in sperm may pave the way for better understanding the molecular pathology of varicocele.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of varicocele in the general adult population is about 15-20%, and it can be considered a major cause of male infertility. Although they probably originate due to valvular absence or incompetence in the internal spermatic veins, varicoceles may occur due to a number of different mechanisms, and is thus considered a multifactorial disease [1,2].…”
Section: Introductionmentioning
confidence: 99%